Analisis Sistem Pinjaman Qardhul Hasan Bank Ziska Kabupaten Ponorogo dalam Pandangan Fatwa DSN-MUI - Choirul Daroji; Yana Dwi Christanti (Civiliza Publishing, 2022)
Ziska Bank is a bank within the meaning of Banking Law no. 10 of 1998 and the Sharia Banking Law no. 21 2008, but Bank Ziska is a financial aid based on Zakat, Infaq, Shodaqoh and other religious social funds. Bank Ziska is an East Java LazisMu program for tasharuf zakat, infaq and shodaqoh funds as well as other religious social funds (Ziska) which are specially managed to empower micro, micro, small businesses and small farmers. The main operation of Ziska Bank is to channel qardul hasan credit to Ziska Bank partners. Ziska Bank is not allowed to raise funds except through Lazismu or Lazismu Service Office (KLL). Qordhul Hasan is a loan without any fees. the customer only pays the principal fee at maturity according to the agreement. This study uses a descriptive analysis method by identifying from various sources including books, journals, websites, al-Qur'an, Hadith so that it can be described that the qordhul hasan credit program at Bank Ziska is in accordance with the DSN-MUI fatwa on qardh. From the results of this study, it can be said that Bank Ziska's qardhul hasan credit program is an oasis for the lower middle class in order to escape from the bondage of moneylenders.